Maintenance work at Apartment Laguna Biru / Muhammad Farid Azmi - Azmi, Muhammad Farid (Universiti Teknologi MARA, Perak, 2016)
Maintenance is a very important thing to elaborate on, therefore this report will discuss the maintenance work in high rise building located at Rawang, Selangor. Every building needs to be inspected to ensure all the building system is in good condition. The objective report is to study the maintenance works at high-rise residential building and to identify the problem that occurs during the maintenance works at the selected case study building. Observations, surveys, readings and research have been done in order to collect information regarding the building maintenance process. Finally, this report will discuss the process of building maintenance for high rise residential houses.